A comparative assessment of redfish in NAFO division 3M on beaked redfish (S. mentella and S. fasciatus) commercial, by-catch and survey data - Ávila de Melo, A.; Alpoim, R.; Saborido-Rey, Fran (Northwest Atlantic Fisheries Organization, 2000)
55 páginas, 17 tablas, 14 figuras.-- Scientific Council Meeting The present assessment evaluates the status of the 3M beaked redfish stock, regarded as a management unit composed of two populations from two very similar species (Sebastes mentella and Sebastes fasciatus). Survey bottom biomass and survey female spawning biomass was recalculated based on the abundance at length from Canadian (1979-85) and EU (1988-99) bottom trawl surveys and on the length weight relationships derived from EU survey data. The analytical assessment used a 1989-99 catch at age matrix starting at age 4 and incorporating the 1993-99 redfish by-catch in the shrimp fishery at age. A Separable analysis (Pope and Shepherd, 1982) coupled with a traditional VPA run was first performed, followed by an Extended Survivor Analysis (Shepherd, 1992), which included a 1999-94 Retrospective Analysis. Both models converge not only on the picture they gave of the biomass trend over the past eleven years but also on the order of magnitude of their annual estimates, ending up with an identical value for the 1999 biomass. A logistic surplus production model (ASPIC) which does not use the equilibrium assumption (Praguer, 1994 and 1995) was finally applied using the 1959-99 catch estimates with the STATLANT commercial catch and effort data (1959-1993) as well as the age 4 plus EU bottom biomass (1988- 1999). These last results, as regards biomass and fishing mortality trends are identical to the VPA based ones though with a faster rate of biomass increase over the final years of 1998-99. Either VPA’s and ASPIC analysis pointed out that the 3M beaked redfish stock experienced a steep decline during the second half of the eighties till 1991 and was kept at a low level during the first half of the nineties. During this former period fishing mortality was kept well above Fmsy, due to extremely high catches from the direct fishery (1989-93) followed by an extremely high level of redfish by-catch in numbers from the 3M shrimp fishery (1993-94), which ...